2017
DOI: 10.1186/s12864-017-3496-x
|View full text |Cite
|
Sign up to set email alerts
|

An empirical fuzzy multifactor dimensionality reduction method for detecting gene-gene interactions

Abstract: Background: Detection of gene-gene interaction (GGI) is a key challenge towards solving the problem of missing heritability in genetics. The multifactor dimensionality reduction (MDR) method has been widely studied for detecting GGIs. MDR reduces the dimensionality of multi-factor by means of binary classification into high-risk (H) or low-risk (L) groups. Unfortunately, this simple binary classification does not reflect the uncertainty of H/L classification. Thus, we proposed Fuzzy MDR to overcome limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Lazzerini et al 17 reported that IL-1β-induced IL-6 production from human cultured osteoblasts might provide a rationale for the possible employment of rosuvastatin in the treatment of osteoporosis. In addition, Lee et al 18 showed that osteoclastogenesis by IL-1β and/or endoplasmic reticulum stress was mainly associated with up-regulation of eIF2α, GRP78, PERK and IRE1, suggesting that it might be a new therapeutic target for osteoporosis. There is increasing evidence that IL-1β might play an important role in the pathogenesis of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lazzerini et al 17 reported that IL-1β-induced IL-6 production from human cultured osteoblasts might provide a rationale for the possible employment of rosuvastatin in the treatment of osteoporosis. In addition, Lee et al 18 showed that osteoclastogenesis by IL-1β and/or endoplasmic reticulum stress was mainly associated with up-regulation of eIF2α, GRP78, PERK and IRE1, suggesting that it might be a new therapeutic target for osteoporosis. There is increasing evidence that IL-1β might play an important role in the pathogenesis of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…2) was performed to analyze the interactions between SNP and SNP in the CHD risk (22). The difference in clinical characteristics among different genotypes was analyzed using the one-way analysis and ANOVA test.…”
Section: Discussionmentioning
confidence: 99%
“…The association was also evaluated in subgroup analyses strati ed by demographic and clinic variables. Multifactor dimensionality reduction (MDR) (version 3.0.2) was performed to evaluate the SNP-SNP interactions in the risk of cervical cancer (14). A two-tailed p-value < 0.05 was considered to be statistically signi cant for all the analyses.…”
Section: Study Participantsmentioning
confidence: 99%